SOCIO-HISTORICAL AND LOGICAL-GNOSEOLOGICAL ANALYSIS OF THE ART OF DISPUTE IN THE HISTORY OF KNOWLEDGE - Тurabova , Sevara (Educational Research in Universal Sciences, 2023)
This article analyzes the functional aspects of the dispute phenomenon as a developing intellectual phenomenon passing through the stages of its emergence, formation and development. Accordingly, the dispute as a source of research and a process of gradual development requires historical analysis. Because the study of the multifaceted problems of discussion culture based on diachronic approaches makes it possible to obtain important heuristic results.